Genetic susceptibility to Theileria orientalis (Ikeda) in Angus- and Hereford-sired yearling cattle born to dairy cattle on an endemically infected farm in New Zealand - Lawrence K; Fermin L; Gedye K; Hickson R; lawrence B; coleman L; Pomroy W; Natalia M; Lopez- Villalobos N (Taylor and Francis Group)
Theileria orientalis (Ikeda) was first detected in New Zealand in 2012, becoming endemic in most of the North Island, and can cause incidences of anaemia and death. Research has been performed in New Zealand on the incidence and severity of infection. Through this research anecdotal evidence has been found to suggest a potential genetic susceptibility component in the response of the host to the parasite. To investigate the genetic susceptibility of cattle to T. orientalis (Ikeda), 99 calves born in 2016 as part of a separate experiment and grown in six grazing herds, were examined for their response to the parasite. In addition to measuring live weight, two blood collections were taken in the first four months of life which were used to measure packed cell volume by haematocrit and qPCR to assess parasite load. Heritability was calculated and was low for parasite load, but the result indicates that there is some potential to increase resistance through selective breeding. The mechanisms of the differences in parasite load were not elucidated in this research; however, significant variation was found among herds and sires, indicating that both genetic selection and environmental management could be utilised to reduce parasite load in growing calves.
Keywords: 0503 Soil Sciences; 0607 Plant Biology; 0703 Crop and Pasture Production